Pengaruh Brand Image Terhadap Kepuasan dan Loyalitas Pelanggan pada PT. Brand X di Jakarta - Santana, Alex; Keni, Keni (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The aim of this study are : First, to explore the effect of brand image on customer loyalty. Second, to explore the effect of brand image on customer satisfaction. Third, to explore the effect of customer satisfaction towards customer loyalty. Fourth, to find out if customer satisfaction can mediate brand image towards customer loyalty. The method of data collection is convenience sampling. The samples of this research are collected from 135 respondens, who are the customers of Brand x in Jakarta. The technique of data analysis used in this study was regression analysis and mediating test to find put the hypotheses. The results are : (a) the effect between brand image have a significant and positive impact toward customer loyalty; (b) the effect between brand image have a significant and positive impact toward customer satisfaction; (c) customer satisfaction has a positive impact on customer loyalty; (d) customer satisfaction will mediate the effect of brand image towards customer loyalty.